Soil Contamination : Threats and Sustainable Solutions - Larramendy, Marcelo L.; Soloneski, Sonia; Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2021)
This edited book, Soil Contamination - Threats and Sustainable Solutions, is intended to provide an update on different aspects of soil contamination exerted by a multiplicity of exogenous and endogenous causes. We hope that this book will continue to increase information from diverse sources and to give some real-life examples, extending the appreciation of the complexity of this subject in a way that may stimulate new approaches in relevant fields.
English
Keywords: Soil science, sedimentology